Diagnostic Accuracy of Electrocardiographic Criteria for Left Ventricular Hypertrophy in Thalassemia Syndrome - Sudigdo Sastroasmoro; Deddy Ria Saputra; Bambang Madiyono; Ismet N. Oesman; Sukman Tulus Putra (Indonesian Pediatric Society, 1995)
We compared the diagnostic accuracy of electrocardiographic (ECG) criteria for left ventricular hypertrophy (LVH) in 119 randomly selected from 400 patients with thalassemia major treated at the Department of Child Health, Medical School, University of Indonesia, Jakarta. Echocardiographically derived left ventricular hypertrophy (EchoLVH), both for body surface area (BSA)-indexed and height-indexed, served as the gold standard. There were 57 girls and 62 boys available, ranging in age from 5 to 27 years. ECG criteria for LVH was detected in 23 outof119 patients, while echo-LVH was detected in 47 patients if BSA-indexed LVH was used, or 22 patients if height-indexed LVH was used. The sensitivity and specificity of ECG-LVH were 25.5 and 84.7% respectively if BSA indexed LVH was used as gold standard, or 36.4% and 84.5%, respectively, when height indexed echo-LVH was used. It is concluded that ECG criteria for LVH has a low sensitivity and hjgh specificity in detecting increased left ventricular mass in children with thalassemia major.